Hubungan Pengobatan terhadap Fungsi Seksual pada Pasien Kanker Serviks di RSUP Dr. Kariadi Semarang - Nadila Dinar Valentina; Rinda Intan Sari; Nella Vallen Ika Puspita (Pusat Riset dan Inovasi Nasional, 2024)
Background: A malignant tumor known as cervical cancer attacks the female reproductive organs around the vaginal mucosa and the cervical canal mucus, also known as the lower part between the vagina and the uterus. Those diagnosed with cervical cancer must receive a variety of treatments, including chemotherapy, radiation therapy, surgery, or multitherapy. The study evaluated the correlation between treatment and sexual function in patients with cervical cancer at Dr. Kariadi's Hospital in Semarang. This cross-sectional research used consecutive sampling to collect samples from 69 participants from March to April 2024. This study used a questionnaire from the Women's Sexual Function Index. (FSFI). The research results showed that of the 69 respondents, the age group that experienced the most sexual dysfunction was 46-55 years old, with 24 respondents (34.8%), the most common treatment for cervical cancer patients was multitherapy treatment with 49 respondents (71%) , and respondents who experienced sexual dysfunction were 64 respondents (92.8%).The results found a significant correlation between treatment and sexual function in patients diagnosed with cervical cancer. The p-value is 0.004 (p < 0.05), and the correlation coefficient is 0.342, indicating an insignificant correlation. Research suggests that interventions can improve the sexual function of cervical cancer patients.